Identification of Key Genes in the Response to Salmonella enterica Enteritidis, Salmonella enterica Pullorum, and Poly(I:C) in Chicken Spleen and Caecum. (22nd February 2014) - Ma, Teng; Chang, Guobin; Chen, Rong; Sheng, Zhongwei; Dai, Aiqin; Zhai, Fei; Li, Jianchao; Xia, Mingxiu; Hua, Dengke; Xu, Lu; Wang, Hongzhi; Chen, Jing; et al.
Abstract : Salmonella enterica Enteritidis ( S. Enteritidis ) and Salmonella enterica Pullorum ( S. pullorum ) are regarded as a threat to poultry production. This study's aim is to characterize the expression profiles in response to three different challenges and to identify infection-related genes in the chicken spleen and caecum. Groups of the Chinese chicken breed Langshan were challenged with either S. Enteritidis, S. pullorum, or poly(I:C). The concentrations of cytokines and antibodies and the Salmonella colonization level of the caecum and liver were detected in each group at 7 days postinfection. Expression microarray experiments were conducted using mRNA isolated from both spleen and caecum. Crucial differentially expressed genes (DEGs) associated with immunity were identified. Four DEGs were identified in spleen of all three challenge groups (RBM16, FAH, SOX5, and RBM9) and different four genes in caecum (SOUL, FCN2, ANLN, and ACSL1). Expression profiles were clearly different among the three challenged groups. Genes enriched in the spleen of birds infected with S. pullorum were enriched in lymphocyte proliferation related pathways, but the enriched genes in the caecum of the same group were primarily enriched in innate immunity or antibacterial responses. The DEGs that appear across all three challenge groups might represent global response factors for different pathogens.